1995
DOI: 10.1111/j.1365-2796.1995.tb01172.x
|View full text |Cite
|
Sign up to set email alerts
|

Hip fractures and the thyroid: a case‐control study

Abstract: Hyperthyroidism is found 2.5-fold more often in hip fracture patients than in controls. Hence, hyperthyroidism appears to be a significant risk factor for hip fracture and should be investigated by clinical and, when necessary, laboratory means in hip fracture patients. In contrast, no increased risk for hip fracture could be detected after exposure to levothyroxine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 35 publications
2
49
1
2
Order By: Relevance
“…Accordingly, hyperthyroidism was found 2.5-fold more often in postmenopausal women presenting with hip fracture than in controls. Among postmenopausal women, risk of hip fracture was significantly higher in patients with overt untreated hyperthyroidism and a history of past hyperthyroidism (Wejda et al, 1995). These findings were confirmed by a prospective follow-up study realized in 9516 Caucasian women, 65 years of age or older (Cummings et al, 1995).…”
Section: Overt Hyperthyroidism and Skeletal Changessupporting
confidence: 70%
See 1 more Smart Citation
“…Accordingly, hyperthyroidism was found 2.5-fold more often in postmenopausal women presenting with hip fracture than in controls. Among postmenopausal women, risk of hip fracture was significantly higher in patients with overt untreated hyperthyroidism and a history of past hyperthyroidism (Wejda et al, 1995). These findings were confirmed by a prospective follow-up study realized in 9516 Caucasian women, 65 years of age or older (Cummings et al, 1995).…”
Section: Overt Hyperthyroidism and Skeletal Changessupporting
confidence: 70%
“…Decreased bone density in hyperthyroid patients tended to normalize under treatment (Wejda et al, 1995, Jodar et al, 1997. The improvement of BMD was noted even though no other specific anti-osteoporotic measures were introduced.…”
Section: Overt Hyperthyroidism and Skeletal Changesmentioning
confidence: 78%
“…Of note, in that study, the risk for hospitalization because of fracture was approximately twofold greater in persons older than 65 years of age with low TSH levels. Another retrospective study (19) found that women with a history of hyperthyroidism or thyroid cancer appeared to have their first fracture earlier than women without thyroid disease, and two recent case-control studies of endogenous hyperthyroidism and fracture had conflicting results (21,48).…”
Section: Discussionmentioning
confidence: 99%
“…Hypothyroidism is a risk factor for falls in elderly individuals (4), and hyperthyroidism has for more than a century been known as a risk factor for osteoporosis (5). Both overt hypothyroidism and hyperthyroidism have been associated with increased risk of fractures in previous studies (6,7,8,9,10,11,12,13,14). Other studies have reported that fractures are more common in persons with subclinical thyroid dysfunction (15,16), and some have found fracture incidence to increase by decreasing thyroid-stimulating hormone (TSH) within the reference range (13,17,18).…”
Section: Introductionmentioning
confidence: 89%